1985
DOI: 10.1037/0022-0167.32.1.104
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sex role orientation and gender on counseling skills training.

Abstract: This study examined the effect of the sex role orientation and gender of counselor trainees on their counseling effectiveness and ability to demonstrate expressive and instrumental counseling skills. Forty-seven counselor education students, enrolled in one semester of counseling skills training, completed the Bern Sex Role Inventory (Bern, 1981a), taped pre-and posttraining quasicounseling sessions, and took a videotape counseling skills exam. Factorial analyses of variances indicated that sex role orientatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

1986
1986
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…Although generalization is also limited by the small number of participants and the analogue nature of the counseling situations, the results of this study extend previous work (Fong & Borders, 1985;Neimeyer & Fong, 1983) concerning the impact of these two variables on counselor performance. The results indicate that when both sex role orientation and self-disclosure flexibility are considered, an estimated 30% of the variance (?=.298) in counseling examination scores is accounted for.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Although generalization is also limited by the small number of participants and the analogue nature of the counseling situations, the results of this study extend previous work (Fong & Borders, 1985;Neimeyer & Fong, 1983) concerning the impact of these two variables on counselor performance. The results indicate that when both sex role orientation and self-disclosure flexibility are considered, an estimated 30% of the variance (?=.298) in counseling examination scores is accounted for.…”
Section: Discussionsupporting
confidence: 68%
“…Examining the use of the counseling skill self-disclosure by undergraduates, Stokes,Childs,and Fuehrer (198 1) reported that only androgynous college students were willing to disclose to intimates, and that they were the most willing to use disclosure overall. More recently, Fong and Borders (1985) reported counseling students' sex role orientation had a significant effect on counseling skills performance. In particular, masculine-oriented trainees were rated as less effective and undifferentiated as more effective than the other sex role orientation groups.…”
mentioning
confidence: 99%
“…That is, what are the appropriate roles for men and women? Furthermore, attitudes toward gender roles also seem to have an influence on counseling skills (Fong & Borders, 1985). Gold and Hawley (2001) examined counseling students' sex roles and attitudes toward gender role flexibility and expected to find these students to have more egalitarian gender role attitudes, when in fact, they did not.…”
Section: Gender Role Attitudesmentioning
confidence: 99%
“…In previous literature, some researchers have suggested that more influential than the individual's gender, is the individual's gender role attitude (Hamburger et al, 1996) Not only has the literature examining attitudes toward women who have been battered closely examined the role of gender role attitudes on perceptions, the extant literature on gender roles has provided strong evidence to suggest that our perceptions and behaviors are heavily influenced by our beliefs about the roles of men and women (McConahay & McConahay, 1977;Sanday, 1981). Gender role attitudes have been shown to influence individuals attitudes toward mental illness (Hinkelman & Granello, 2003), perceptions of men and women (Kernes & McWhirter, 2001), and even counselor skill development (Fong & Borders, 1985).…”
Section: Summary Of Counselors' Perceptions Of Women Who Have Been Bamentioning
confidence: 99%
“…Although counseling research has freq~ently studied sex of counselors-tn-tratntng and performance of selected skills, the fmdings are inconclusive (Borders & Fong, 1984). Limited attention has been given to the relationship between gender role orientation and counselor effectiveness, and its impact is poorly understood (Borders & Fong, 1984;Cook, 1987;Fong & Borders, 1985). For example, Fong and Borders (1985) found that undifferentiated counselors were rated as most effective but not significantly more effective than androgynous and feminine counselors, whereas masculine counselors were rated as significantly less effective than the other three.…”
mentioning
confidence: 99%